Penerapan Teknik Kompres Daun Kubis Dalam Mengurangi Nyeri Dan Pembengkakan Payudara Pada Ibu Post Partum Di Wilayah Kerja Puskesmas Limboto - Massa, Desy Anggriani; Firmawati (Jurnal Keperawatan Muhammadiyah, 2025)
Background: In general, breast pain and swelling are normal for post partum mothers at the beginning of breastfeeding after giving birth, where at the beginning of breastfeeding, the baby is still not adequate for breastfeeding so a lot of milk will accumulate in the breasts which causes the breasts to become swollen and painful, but even though this condition is considered normal, but if not treated properly it can cause complications in the form of mastitis (Salat & Indriyani, 2019). To treat breast pain and swelling, namely cold cabbage leaf compresses, warm compresses and manually expressing breast milk. This study aims to determine the application of the cabbage leaf compress technique in reducing pain and breast swelling in post partum mothers in the Limboto Health Center Working Area. Methods: This research uses a quasi-experimental research design using the one group pretest-posttest design method. The research object is post-partum mothers who are in the working area of the Limboto health center. The subjects in this case study were 15 patients. The research instrument used an observation sheet using the NRS or Numeric Rating pain measurement scale observation sheet and the breast swelling scale, namely SPES or Six Point Engorgement Scale. Results: Based on the results of statistical tests using the Wilcoxon test, it was found that the average pain scale value before was 4.40 (SD 1.298) and after was 0.20 (SD 0.775) with a p-value of 0.001 < α 0.05 and the average swelling scale before was 4.67 (SD 0.617) and after is 1.80 (SD 0.862) with p-value 0.000 < α 0.05 Conclusion: There were a significant difference between the average pain and swelling before and after applying the cabbage leaf compress technique so that it is found that the cabbage leaf compress technique can be applied in reducing pain and breast swelling in post partum mothers in the Limboto Health Center Working Area.